The impact of the use of block chain technology in improving the efficiency of the Iraqi banking sector (المجلة العراقية للعلوم الاقتصادية, 2024)
This research aims to measure the impact of the use of blockchain technology in improving the efficiency of the Iraqi banking sector. And its role in reducing the cost of banking services and developing them in the financial sector, represented by Iraqi banks. The extent to which the research sample accepts the adoption of this technology. The research community represents some Iraqi banks in Baghdad. There are ten banks with various branches, and these banks were represented by the following (five branches of Al-Rasheed Bank. Four branches of Al-Rafidain Bank, and Al-Taif Islamic Bank). The number of questionnaires distributed to auditors was (68), and (64) were retrieved, representing (94.1%). The remainder of the questionnaires, amounting to (4), i.e. (5.9%), are not suitable for statistical analysis and were analyzed using the SPSS statistical program. Where the blockchain technology will increase efficiency and economic returns and reduce costs and financial burdens. The results of the research concluded that blockchain technology represents the best technical solutions currently available. To reduce the material costs of operations in the financial sector. As well as, speeding up financial transactions. While ensuring the safety of financial transactions and transactions, and reducing manual procedures. It Contributes to meeting the needs of the financial sector of banks by eliminating the need for intermediaries, saving a measure of time and money helping reduce the operational cost to the lowest cost and improve the capital. It also contributes to enhancing transparency within the sector. Eliminating opportunities for human error in providing banking services, which ultimately contributes to enhancing operational efficiency and improving the quality of banking services provided to customers. The most prominent recommendations of the research were the need for Iraqi banks to rely on blockchain technology which contributes to reducing the cost of banking services, raising operational efficiency and taking effective measures to support its application